2020
DOI: 10.3389/fimmu.2020.00423
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Fingerprints of Borderline Changes in Kidney Allografts Are Influenced by Donor Category

Abstract: down-regulated transcripts included proline-rich 35 (PRR35) and fibroblast growth factor 9. Early borderline changes in ECD kidney transplantation are characterized by increased regulation of inflammation, extracellular matrix remodeling, and acute kidney injury transcripts in comparison with both LD and SCD grafts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The upregulation of CCL13 expression is a result of pro-inflammatory cytokines in response and plays an important role in monocyte/macrophage recruitment and retention in renal inflammation ( 10 ). In addition, kidney donor quality significantly affects renal transplantation outcomes, such as recipients of kidney donors from the elderly who exhibit low post-transplant renal function and short graft lifespan; a single-center, retrospective, observational study showed that compared to standard criteria donors and living donors, elderly and expanded criteria donors have upregulated CCL13 at the transcriptional level and may be involved in post-transplant renal inflammation and renal function impairment ( 77 ).…”
Section: Ccl13 and Renal Diseasesmentioning
confidence: 99%
“…The upregulation of CCL13 expression is a result of pro-inflammatory cytokines in response and plays an important role in monocyte/macrophage recruitment and retention in renal inflammation ( 10 ). In addition, kidney donor quality significantly affects renal transplantation outcomes, such as recipients of kidney donors from the elderly who exhibit low post-transplant renal function and short graft lifespan; a single-center, retrospective, observational study showed that compared to standard criteria donors and living donors, elderly and expanded criteria donors have upregulated CCL13 at the transcriptional level and may be involved in post-transplant renal inflammation and renal function impairment ( 77 ).…”
Section: Ccl13 and Renal Diseasesmentioning
confidence: 99%
“…ECD-related transcripts were likely increased by already occurred vascular changes compared to SCD group, and, similarly in SCD group, by longer ischemia compared with LD group. Therefore, chronic vascular changes and cold ischemia time enhance inflammation and thus contribute to poor outcomes for these grafts [57].…”
Section: Transcriptomics/genomicsmentioning
confidence: 99%
“…Although most studies have examined complement activation in standard DBD donors, intuitively, the degree of inflammation and thus complement activation may be more profound in DCD and extended criteria donors. Accordingly, comparisons of transcriptional profiles and histology have shown increased activation of inflammatory chemokines, complement, and coagulation in DCD and extended criteria kidneys, compared to standard criteria donors ( 34 , 35 ).…”
Section: The Role Of Complement System In Irimentioning
confidence: 99%